A Survey of the Riparian Vertebrate Fauna of Señora River, Siquijor Island, Central Philippines - Alcala, Michael Lawton R.; Basa, Jocelyn Elise P.; Sequihod, Irish; Pagente , Albert; Kilat, Will; Catid, Rosalina E.; Bucol, Abner A. (Silliman Journal, 2022)
An assessment on the status of the riparian vertebrates of Señora River in Siquijor Island was conducted from February-May, 2011 using purposive sampling techniques. This study observed 40 species of birds, five species of amphibians, 13 species of reptiles, and 10 species of mammals.